How to avoid hardships in life know the secrets of the practices and teachings of Islam that had led the muslim ummah to become successful and progressive who carried the torch of knowledge and development for all people - Ahmad Haris Suhaimi (Nusantara Books, 2021)
In this book, we shall try to identify the practices and teachings of Islam that had led the Muslim ummah to become successful and progressive. Similarly, we shall also identify things that we should be mindful of to prevent any untoward incidents or calamities. This miracle is what we need to study and learn. All these indicate that Islam has countless benefits and secrets that we need to discover to answer life's questions. We can use the answers to regain our achievements and glory, and for the Muslim ummah.